Adult ESL and Literacy : Issues and Options - Spruck Wigley, Heide (The Centre for Literacy of Quebec (CFL), 2008)
In this paper, I would like to put forward a number of issues for us to think about and discuss. At the same time, I argue for a better articulated system that more closely matches the needs and goals of various subgroups of English language learners.

Understanding Literacy and Family Literacy Needs of Anglophone Adults in Quebec : Research Summaries - The Centre for Literacy of Quebec (CFL) (2011)
The Understanding literacy and family literacy needs of Anglophone adults in Quebec project aimed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve English-speaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities which showed large disparities in literacy performance among Quebec Anglophones. The findings suggested differences in need from one community to another that may require targeted services. This project set out to fill this knowledge gap and to insert LES into the ongoing discussion about Anglophones in Quebec. All Quebec English-language umbrella groups stand to benefit from the findings in terms of proposing better policy, planning new services and using resources more efficiently. There may be opportunities for new partnerships to develop solutions to some challenges not previously seen as linked to literacy. The project will also provide a useful road map for identifying promising new research avenues that would assist LES organizations in getting a more detailed picture of the communities they are aiming to serve.